HUBUNGAN IKLAN POP-UP YOUTUBE DENGAN SIKAP USER (PENGAKSES) - Oktaviani, Resti; Nurnawati H.H, Bedjo Sukarno, (Solidaritas, 2017)
HUBUNGAN IKLAN POP-UP YOUTUBE DENGAN SIKAP USER (PENGAKSES)(Studi Korelasi Iklan Pop-up Youtube dengan Sikap User Mahasiswa Jurusan Teknik Informatika Universitas Surakarta)  Oleh :Resti Oktaviani, Drs. Bedjo Sukarno, M.Si , Dra. Nurnawati H.H, M.Si  AbstractPop-up ads on social media, like youtube is chosen as one of the advertising media. This study aims to determine the relationship between advertising and pop-ups with attitude youtube user (Accessors) in students majoring in Engineering Informatics, Surakarta University (UNSA). This study took a sample of 70 students from 223 students, using Simple Random Sampling technique. The results of the research shows that there is a relationship between pop-up ads with the attitude of youtube users (Accessors) in students majoring in Engineering Informatics, Surakarta University (UNSA). Youtube pop-up ads that viewed of duration, language, and frequency while the attitudes that viewed of attention, cognitive and affective of the Informatics Engineering students. Keyword : pop-up ads, attitude user (accessor), youtube